Reliability Analysis of Fire Water Line - Sutrisno, Sutrisno; Ariwibowo, Didik; Darmanto, Seno; Mangestiyono, Wiji; Saputra, Galih Satria Hendri (Vocational College of Universitas Diponegoro, 2020)
The purpose of this research is to analyze the reliability of firewater as a water distribution for emergency conditions. To determine the remaining useful life (RUL) of the firewater line, this research will apply the counting process so that the rate of remaining useful life (RUL) of the firewater line can be known. The data used as the basis for calculation is failure data gained from technical division databases from 2018. The data obtained will be processed using visual inspection and ultrasonic thickness test methods to produce the remaining useful life of the firewater line. From 5 example fire water lines, only 3 needed to replace of firewater line cause less than 10 years. RUL to 9 years at 10” and 12” Train C/D, 2.45 year at 14” Train C/D, 8 years at 10” and 12” Utilities I. The mathematical modeling will be verified using visual thickness and ultrasonic Test method to ensure Remaining useful life of firewater line at Badak LNG. Visual inspection refer to API 571 and ultrasonic test refer to API 570 and ASME B31.3